Smart Structures, Devices, and Systems 2002
DOI: 10.1117/12.479821
|View full text |Cite
|
Sign up to set email alerts
|

Practical issues in the implementation of electro-mechanical impedance technique for NDE

Abstract: The electro-mechanical impedance (EMI) technique, which utilizes 'smart' piezoceramic (PZT) patches as collocated actuator-sensors, has recently emerged as a powerful technique for diagnosing incipient damages in structures and machines. This technique utilizes the electro-mechanical admittance of a PZT patch surface bonded to the structure as the diagnostic signature of the structure. The operating frequency is typically maintained in the kHz range for optimum sensitivity in damage detection. However, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 13 publications
1
42
0
5
Order By: Relevance
“…Once the measurement was performed, the data was sent wirelessly to an XBee modem that was Three different parts of an impedance measurement were recorded: real impedance, imaginary admittance and impedance magnitude. The real impedance is used in impedancebased SHM as the primary damage detection measurement, because it is more sensitive to damage or changes in the structure [9,14]. The imaginary admittance measurement is used for sensor diagnostics, because the slope of the imaginary admittance line varies with PZT sensor condition [10,6], which would include sensor debonding and sensor breakage.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the measurement was performed, the data was sent wirelessly to an XBee modem that was Three different parts of an impedance measurement were recorded: real impedance, imaginary admittance and impedance magnitude. The real impedance is used in impedancebased SHM as the primary damage detection measurement, because it is more sensitive to damage or changes in the structure [9,14]. The imaginary admittance measurement is used for sensor diagnostics, because the slope of the imaginary admittance line varies with PZT sensor condition [10,6], which would include sensor debonding and sensor breakage.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…The theory has been substantially developed by Park et al [6,7,8], Bhalla et al. [9,10], Giurgiutiu et al [11,12,13] and Sun et al [14].…”
Section: Impedance-based Structural Health Monitoringmentioning
confidence: 99%
“…By affixing PZT sensor to critical section of the bridge. In 2002, Bhalla et al and Naidu et al monitored the initial damage of concrete structure by using the EMI technique, and meanwhile they have also monitored the strength increase of concrete during curing by using the EMI technique and obtained the correlation between concrete stiffness and the peaks value of the EMI signal [5][6][7]. In 2002-2005, Giurgiutiu et al performed the structural online health monitoring in conjunction with the EMI technique and Lamb wave sensor into the structure.…”
Section: Introductionmentioning
confidence: 99%
“…air, gel, water)), ((Brunner et al, 2004), p10), ((Schubert and Herrmann, 2012), p3635), semi-permanent ( (Bhalla et al, 2002), p492), ((Chetwynd et al, 2006), p302), or permanent ( (Bhalla et al, 2002), p492), ((Paget et al, 2003), p367).…”
Section: Surface Attachment Methodsunclassified
“…Semi-permanent attachment of transducers using double sided adhesive tape was investigated by Bhalla et al (2002), (p492) and found to produce poor coupling with the host structure. Chetwynd et al (2006), (p306) found that a thin viscoelastic layer in the form of double sided tape to be successful even though it is a softer material than conventional epoxy adhesive.…”
Section: Surface Attachment Methodsmentioning
confidence: 99%